Contributions of a social technology from the perspective of men being sued for gender violence - Fernanda Matheus Estrela; Nadirlene Pereira Gomes; Andrey Ferreira da Silva; Milca Ramaiane da Silva Carvalho; Júlia Renata Fernandes de Magalhães; Álvaro Pereira; Evaldo Almeida da Silva (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to discover what were the contributions of the Reflexive Group from the perspective of men being sued by marital violence, who participated in a social technology. Methods: qualitative study, resulting from the evaluation stage of an action-research, based on the perspective of Critical Freedom and carried out with 44 men who were being sued in the Peace at Home Courts, in Salvador, Bahia, Brazil. Results: the discourses of men being sued for marital violence showed that the reflections enabled them to share their experiences; understand their attitudes as disrespectful, violent, and liable in criminal courts; elaborate of strategies for a harmonious marital life; and become multipliers as a result of their willingness to socialize the information and knowledge that emerged from their group. Conclusions: the study presents a successful experience of the participation of men in reflexive groups and is a precedent for the validation of this social technology.